Eine modulare Funktionsarchitektur zur Umsetzung einer gesamtheitlichen Betriebsstrategie für Elektrofahrzeuge - Basler, Alexander (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
Due to the low energy content of the high-voltage traction battery, the range of battery electric vehiclesis currently restricted. Compared to conventional vehicles, the range is significantly lower. Thus, using a battery electric vehicle everyday might result in a complex conflict of objectives between range, dynamic and comfort requirements.For this purpose, this study develops a holistic system approach, in order to implement and apply range-extending functionalities.